TINGKAT INTEGRASI PASAR MODAL INDONESIA DENGAN PASAR MODAL GLOBAL - Saputra, Dedy (Manajemen Bisnis, 2014)
This study aims to determine the level of capital market interation Indonesia (Jakarta Composite Index) with American capital markets (Dow Jones Industrial Average), England (FTSE 100 Index), German (Deutsche Borse AG German Stock Index), Hongkong (Hang Seng) and Japan (Nikkei 225). The result of this study expected to become an information for investment actors in deciding to invest at the stockmarket. These variables include the Indonesian capital market as the dependent variable and the global capital markets as an independent variable. Analysis tool is the correlation coefficient and t test. It is used to determine the significance of the correlation coefficient between independent variables and the dependent variable. Based on the calculation of the correlation coefficient is exemplified that the market index Indonesian capital market and the five major global capital markets has been integrated on various classification levels of relationships or different integration. The level of integration between Indonesian capital market and capital markets of America and Japan are very strong level of integration, the German stock market has stronglevel integration, and England and Hong Kong capital market has low level integration.